Pengaruh Karakteristik Pekerjaan Dan Kecerdasan Emosional Terhadap Kualitas Kerja Pegawai Pada Badan Pengelolaan Keuangan Dan Aset Daerah (BPKAD) Kota Bima - Wanda Widiartiningsih; Rahmatia Rahmatia; Firmansyah Kusumayadi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the influence of job characteristics and emotional intelligence on employee work quality at the Regional Financial and Asset Management Agency (BPKAD) of Bima City. Employee work quality is a crucial aspect in achieving organizational goals and is influenced by internal factors, including perceptions of job characteristics and individuals’ ability to manage emotions. This research employs a quantitative method with an associative approach. The population of the study consists of all employees at BPKAD Bima City, with samples selected through purposive sampling. Data collection was conducted through questionnaires. The data obtained were analyzed using multiple linear regression. The results indicate that job characteristics have a positive and significant effect on employee work quality. Likewise, emotional intelligence also has a positive and significant effect. This implies that the better the perceived job characteristics and the higher the emotional intelligence of employees, the better their work quality. Therefore, management is advised to continuously improve job design and provide emotional intelligence training to enhance overall employee performance.